An Integral Cultural Space in Europe and New Challenges for its Economic Development - Melnikas, Borisas (Ekonomika, 2007)
The paper aims to evaluate the main features of the creation and development of an integral cultural space in Europe and the main problems of economic development in the context of the enlargement of the European Union and the transition processes in Central and Eastern Europe. The author has used the outcomes of the research done over the recent several years, dedicated to the diagnostics of the problems of transformations as well as economic and social development in Central and Eastern Europe with a special reference to the development of the integral cultural space and human rights in the context of economic development in the European Union. The major findings show that the creation and development of the integral cultural space in Europe is a very complex and controversial process, and in its course various problems and conflicts arise. Therefore, to encourage the creation of the integral cultural space in Europe, appropriate cultural policies are necessary to be implemented. These policies may embrace many priorities including - preservation of cultural diversity; - adaptation and dissemination of integrated European dimensions; - elimination of inappropriate factors within humanism and democracy of all European countries; - provision of equal rights for all groups of modern society. For implementation of key priorities of cultural policies, the use of a number of special pan-European programmes is suggested. The new non-traditional ideas of a possible economic and social development in Central and Eastern Europe are discussed.